PENGARUH IMPLEMENTASI KEBIJAKAN PENATAAN RUANG TERBUKA HIJAU (RTH) DAN PENGELOLAAN TAMAN KOTA TERHADAP KEPUASAN PUBLIK PENGGUNA TAMAN KOTA DI KOTA SUKABUMI - Gemiarty Puteri Yuanita Betha Anugerah; Ute Chairuz M. Nasution (PRAJA observer: Jurnal Penelitian Administrasi Publik (e- ISSN: 2797-0469))
The Sukabumi City Public Green Open Space (RTH) currently has an area of 7% of the Sukabumi City area. Of course, this is still less than the percentage that has been stipulated by Law number 26 of 2007 concerning Spatial Planning where public green open space must have an area of at least 20% of the city area. The research uses a quantitative approach with associative descriptive research design through survey methods. Sampling using an accidental sampling technique. The theoretical basis used is the implementation model theory of Edward III, management theory according to George R. Terry, and public satisfaction theory according to Kottler. The research instrument used a questionnaire with a rating scale. Data analysis was done descriptively and statistical test of product-moment correlation, coefficient of determination, and regression equation. The results of the descriptive analysis show that the implementation of the policy on providing green open space is in the Good Enough category, the management of city parks is in a Good category, and public satisfaction of city park users is in the Good category. The results of the correlation coefficient are in the medium category, and the results of the regression test are positive. The results of these statistical tests after testing the hypothesis indicate that there is a positive and significant relationship between the implementation of the policy of providing green open space and the management of urban parks on public satisfaction of city park users in the city of Sukabumi. Based on the results of these studies, it can be concluded that the implementation of the policy of providing green open space and managing city parks has a positive and significant effect on public satisfaction of city park users in the city of Sukabumi.